If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -9 + x = 0 Reorder the terms: -9 + X + x = 0 Solving -9 + X + x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '9' to each side of the equation. -9 + X + 9 + x = 0 + 9 Reorder the terms: -9 + 9 + X + x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + X + x = 0 + 9 X + x = 0 + 9 Combine like terms: 0 + 9 = 9 X + x = 9 Add '-1x' to each side of the equation. X + x + -1x = 9 + -1x Combine like terms: x + -1x = 0 X + 0 = 9 + -1x X = 9 + -1x Simplifying X = 9 + -1x
| -28=16x-(8x-11) | | log(25x)=0 | | 24-16x+20x-9=31 | | 5x+1=35-x | | y(t)=5+10cos(30t)+15cos(90t) | | -2(2m+-1)+4m= | | -28=18x-(3x-9) | | 8z+17=7z+10 | | 3y+y+88=180 | | 0.6(3x+9)=2.5-(x-3) | | 4m-5=2+m | | 2+10x=-7+x | | -7=3-(5-b) | | 6x+35+8x-23=180 | | 18x-4x-12-10=26 | | 2x-7+4x=-43 | | 51x(x-3)+6=5x-9 | | 4x+95=y | | 8x+7=2x+5 | | -4p+3=15 | | 45n+45y= | | 8m+7=87 | | p=460ftw+30 | | n+(n+1)+(n+2)+(n+3)=-92 | | 50-3x=14-7x | | 1/16=x^2 | | -6y+7x=-2 | | 6-3(-2-4x)=2(3(x-4)+7) | | x-(5/16)=(9/16) | | ln(y-49)=3x | | 6(x-2)=2(x-22) | | (-x/5)=-4 |